CLIMATRIAL: applicability and adaptability of a novel method to quantify the carbon footprint of a South African clinical trial - Nandi Louise Siegfried; Lesley-Ann Erasmus-Claassen; Jessica Griffiths; Lisa Fox; Paula R. Williamson (Trials)
Abstract Background No formal assessment of a method to measure the carbon emissions from a clinical trial has been undertaken in the low- and middle-income country setting. We aimed to evaluate the UK-based National Institute of Health Research (NIHR) method for tracking trial emissions for applicability and adaptability to the South African context. Objectives included to (1) identify gaps in trial activity data, (2) locate local emission factor sources, (3) quantify emissions and (4) investigate modifications required to ensure the method was locally applicable. Method We adopted an application and implementation approach. We established a formal stakeholder structure focused on sustainable clinical trials to guide and support our approach. We selected a large cluster-randomised trial of a health service delivery intervention conducted across multiple urban and rural sites as an exemplar typical of local conditions to test the NIHR method. We created a trial process map outlining ten recommended activity stages for carbon emissions and an Excel workbook to calculate emissions for each stage. We prioritised calculations of those activities for which we had the most complete data: paper usage and printing, local travel between sites, and electricity consumption at the trial head office and at trial sites. We extracted activity data from organisational financial instruments. Results The study took place between December 2023 and March 2024. We identified a lack of publicly available local emission factor sources. Paper usage and printing activities took place at trial set-up and during intervention delivery and emitted 2274.88 kgCO2e. Field staff travel between trial sites during intervention delivery and follow-up resulted in approximately 80,000 km travelled between 2016 and 2019 contributing 17,891 kgCO2e. Electricity consumption was based on full-time equivalent staff and yielded 12,515 kgCO2e during the 4-year period. We observed large differences between UK and available SA emission factors with SA emission factors far higher than those in the UK. Conclusion We found that with minor modifications, the NIHR guidance is applicable to the SA context. It is a highly adaptable framework permitting tracking of activities across trial stages. A lack of locally available emission factors reduces accuracy and emission results should be viewed as indicative.